Children’s Hope in South Africa: A Population-Based Study - Savahl, Shazly (Frontiers in Psychology, 2020)
A growing body of research has provided evidence for the cognitive motivational construct of hope as a psychological strength, particularly for children in adverse social circumstances. In children, hope is defined as a set of cognitions focused on children’s agency to contemplate workable goals, to identify pathways to achieve those goals and the intrinsic beliefs about their capacity to activate sustained movement toward those goals. Using data from the third wave of the Children’s Worlds International Survey on Children’s Well-Being, the study aimed to explore children’s hope amongst a random population-based sample of children in South Africa. The study further aimed to explore children’s level of hope across the nine provincial regions of South Africa. Data were collected using Snyder’s (1997) Children’s Hope Scale. Confirmatory factor analysis was used to analyse the data, with multi-group confirmatory factor analysis used to analyse the data across provincial regions. The study found an appropriate fit structure for the Children’s Hope Scale using the overall pooled sample. The mean score on the Children’s Hope Scale for the national sample was of 4.781 (sd = 1.082). Measurement invariance demonstrated the tenability of scalar invariance, which indicates comparability across correlations, regressions and mean scores. Mean scores ranged from 4.511 (sd = 1.163) for the Northern Cape to 4.982. (sd =.974) for the Western Cape. Five provinces (Eastern Cape, Northern Cape, Free State, Mpumalanga and KwaZulu Natal) scored below the national mean, while four provinces (North West, Western Cape, Limpopo and Gauteng) scored above.